Development and validation of a stability indicating HPLC-diode array-fluorescence method for the determination of meclofenoxate hydrochloride and p-chlorophenoxyacetic acid - Marwa Said Moneeb, Feda Elgammal, Suzy Mohamed Sabry (Journal of Applied Pharmaceutical Science, 2016)
The present work deals with the development and validation of a stability indicating HPLC-diode array-fluorescence method (HPLC-DAD-FL) for the determination of meclofenoxate hydrochloride (MFX) and its hydrolytic degradation product p-chlorophenoxyacetic acid (pCPA). The chromatographic separation was achieved using a reversed phase Zorbax Eclipse SB-C18 column (250 x 4.6 mm i.d., 5 μm particle size), a mobile phase composed of 20 mM phosphate buffer, adjusted to pH 3, and acetonitrile (65: 35, v/v); and isocratic flow at a rate of 1 mL min-1.The detection was carried out using a diode array detector (DAD) at 225 nm and a fluorescence detector (FL) at λex/em, 225/310 nm. The linear dynamic ranges were found to be 0.5-100 and 0.25-100 μgmL-1 (DAD); and 0.05-20 and 0.01-8 μg mL-1 (FL) for MFX and pCPA, respectively. Detection limits were 0.05 and 0.04μgmL-1 (DAD); and 0.005 and 0.001 μg mL-1 (FL) for MFX and pCPA, respectively. The investigated method was applied to the assay of MFX in tablets and vials dosage forms and also to the kinetics stability studies of MFX in different media. Further, the dissolution rate of the tablets was examined using the proposed method.
Keywords: Meclofenoxate,p-chlorophenoxyacetic acid, stability indicating HPLC, kinetics, Dissolution, fluorimetric detection.